Mapping, temporal dynamics, and assessment of agricultural ecosystem services: evidence from eastern India - Rath, Suvangi; Das, Amarendra; T. M., Kiran Kumar; Sarangi, Khitish Kumar (Frontiers in Sustainable Food Systems, 2023)
The study of ecosystem services (ES) has been gaining momentum for two main reasons-first to quantify the ES that the humans are enjoying; second, to incentivize the people or institutions that contribute to the improvement of ES. Agriculture, as the dominant form of land management, acts as both a provider and consumer of ES. The present study is an attempt to map the ecosystem services and assess the agricultural ecosystem services in the village landscape of eastern India. The study aims to understand the various ES, linkages, and trade-offs that have affected the welfare of households in an area of eastern India over time. We found that Jamujhari, the village investigated, had a diverse ecosystem that produced over 60 ecosystem goods, and provided over 200 ecosystem services to the villagers. Moreover, the village’s four ecosystems, viz., forest, water, grassland, and agricultural ecosystems, along with human resources, are integrated and interdependent. However, the ES and the dependence of households on nature’s services have undergone substantial changes over time. The valuation of agroecosystem services (paddy and fallow land ecosystems) was done using the benefit transfer method. The value of the ES for the rice ecosystem was estimated to be US 37892.3 year-1, while under fallow land it was US 9667.8 year-1. resulting in a total value of US 47560.1 year-1 of total agroecosystem services. We suggest comprehensive research to develop context-specific tools to identify and measure ES. Further, we recommend an appropriate policy mix by considering synergies and trade-offs among different ES.